1984
DOI: 10.1677/joe.0.1010163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a long-acting analogue of LH releasing hormone on human and rat corpora lutea

Abstract: Dispersed luteal cells were prepared both from samples of human corpora lutea obtained during normal menstrual cycles and from luteinized rat ovaries of animals pretreated with pregnant mare's serum gonadotrophin and human chorionic gonadotrophin (hCG). Addition of the long-acting analogue, D-Ala6-des-Gly10-LH releasing hormone ethylamide (D-Ala6-LHRH), to rat luteal cells caused a small but significant increase in progesterone production. An inhibitory action of the analogue on hCG-stimulated steroidogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Very high concentrations of mammalian GnRH or its analogues were needed to bind to the receptor or to produce progesterone inhibition. In many studies of the ovarian receptor, the affinity of mammalian GnRH was low (ϳ10 Ϫ6 ) [10,38,39]. Only after cells are in culture for 4 days have low concentrations produced a response [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Very high concentrations of mammalian GnRH or its analogues were needed to bind to the receptor or to produce progesterone inhibition. In many studies of the ovarian receptor, the affinity of mammalian GnRH was low (ϳ10 Ϫ6 ) [10,38,39]. Only after cells are in culture for 4 days have low concentrations produced a response [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The correlations between GnRH agonist binding and a number of important indices of luteal function suggest a physiological role for GnRH-like factors in the human corpus luteum. INTRODUCTION We have demonstrated specific binding of gonadotrophin-releasing hormone (GnRH) and its agonist analogues to human corpus luteum homo- (Clayton & Huhtaniemi, 1982;Richardson, Hirji, Thompson & Masson, 1984) had certain crucial differ¬ ences in binding assay methodology which probably account for the differences observed (Fraser, Bramley, Miller & Sharpe, 1986). Human luteal GnRH binding sites had an impressive specificity for GnRH and its analogues (Bramley, Menzies & Baird, 1986) and, like rat pituitary and gonadal receptors, required both the N-and C-terminal regions of the molecule for binding.…”
mentioning
confidence: 99%
“…A significant decrease in progesterone secretion was reported following incubation of 1 0 -9~ agonist for 96 h (Tureck et al 1982) but other studies found ~O-'M agonist or native LHRH had no effect on FSH stimulated oestrogen and progesterone secretion (Casper et al 1982). Basal and hCG-stimulated progesterone release from cultured human luteal cells was unaffected by agonist (Casper et al 1984;Richardson et al 1984). Finally, M D-Trp6-LHRH did not alter the gonadotrophinstimulated increase in adenyl cyclase activity in a cell-free system prepared from human corpus luteum cells (Rojas & Asch 1985).…”
Section: Direct Gonadal Effectsmentioning
confidence: 98%
“…Specific binding of iodinated LHRH to human luteal tissue has been reported demonstrating only low affinity binding sites (Popkin et al 1983). Others have failed to find even this low level of binding in human (Clayton & Huhtaniemi 1982;Richardson et al 1984) or non-human primate gonadal tissue (Asch et al 1981).…”
Section: Direct Gonadal Effectsmentioning
confidence: 99%